Carbon monoxide poisoning from waterpipe smoking: a retrospective cohort study - Eichhorn, Lars; Michaelis, Dirk; Kemmerer, Michael; Jüttner, Björn; Tetzlaff, Kay (Clinical toxicology (Philadelphia, Pa.), 2018)
Objective: Waterpipe smoking may increasingly account for unintentional carbon monoxide poisoning, a serious health hazard with high morbidity and mortality. We aimed at identifying waterpipe smoking as a cause for carbon monoxide poisoning in a large critical care database of a specialty care referral center. Methods: This retrospective cohort study included patients with a history of exposure to waterpipe smoking and carbon monoxide blood gas levels >10% or presence of clinical symptoms compatible with CO poisoning admitted between January 2013 and December 2016. Patients' initial symptoms and carbon monoxide blood levels were retrieved from records and neurologic status was assessed before and after hyperbaric oxygen treatment. Results: Sixty-one subjects with carbon monoxide poisoning were included [41 males, 20 females; mean age 23 (SD ± 6) years; range 13-45] with an initial mean carboxyhemoglobin of 26.93% (SD ± 9.72). Most common symptoms included syncope, dizziness, headache, and nausea; 75% had temporary syncope. Symptoms were not closely associated with blood COHb levels. Conclusion: CO poisoning after waterpipe smoking may present in young adults with a wide variability of symptoms from none to unconsciousness. Therefore diagnosis should be suspected even in the absence of symptoms.